Development of K13 Learning Media Materials for History Subject at SMA Muhammadiyah 2 Genteng, Banyuwangi - Vini Rahmawati; Putri Candraningtyas (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2023)
Knowing the transitional period of the current curriculum is quite a complex challenge. A popular learning media in schools is the use of class 12 case study learning videos, such as videos about history lessons that present past history in the present. The purpose of the observation is to find out how the learning conditions in SMA Muhammadiyah 2 Genteng are. Based on the results of observations and interviews, the application of the method cannot be separated. The quantitative method uses data collection techniques obtained by observing the learning environment at SMA Muhammadiyah 2 Genteng, conducting interviews and observing how the teacher performs in front of the class. This study uses quantitative research that focuses on learning media from which statistical data is collected. The learning conditions at SMA Muhammadiyah 2 Genteng still use the 2013 curriculum but have included values from the independent curriculum. Students are familiar with modules (electronic and non-electronic) during a pandemic, so this material can be utilized. The learning media used are learning videos, power points, and case studies. It can be concluded that learning is very dependent on the curriculum used.